1987
DOI: 10.3382/ps.0661750
|View full text |Cite
|
Sign up to set email alerts
|

Rearing Early Maturing Pullets

Abstract: A number of experiments were undertaken using White Leghorn pullets to determine the effect of diet and growing treatment on 16-wk body weight and carcass composition. Irrespective of the level of dietary energy, body weight gain and carcass composition appeared to be closely correlated with energy intake of the pullets. Diets as low as 15% protein with and without methionine supplementation resulted in 16-wk body weights similar to those of animals fed diets containing 21% protein, suggesting that protein is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
8

Year Published

1991
1991
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 23 publications
1
7
0
8
Order By: Relevance
“…Além disso, diversos autores já afirmaram previamente que a composição do corpo é o fator mais importante que o peso corporal como indicador do preparo do organismo da poedeira para a produção de ovos (13) .…”
Section: Resultsunclassified
“…Além disso, diversos autores já afirmaram previamente que a composição do corpo é o fator mais importante que o peso corporal como indicador do preparo do organismo da poedeira para a produção de ovos (13) .…”
Section: Resultsunclassified
“…In this respect, Summers et al (1987) and Renema et al (1999b) reported a positive relation between BW of the hens and the maturation of the reproductive traits and the onset of egg production. In the current research, hens that received crumbles during the rearing phase were heavier at 17 wk of age and started egg production sooner (data not shown) and laid more eggs (0.913 vs. 0.898) that were heavier (56.2 vs. 55.4 g) from 17 to 22 wk of age than hens that were fed mash, although the differences did not reach significance.…”
Section: Rearing Phase Dietsmentioning
confidence: 99%
“…Diversos autores têm afirmado previamente que a composição do corpo é fator mais importante que o peso corporal como indicador do preparo do organismo da poedeira para a produção de ovos (WELLS, 1980, JONHSON et al, 1985, SUMMERS et al, 1987.…”
Section: Fase De Posturaunclassified